Analysis of Empowerment and Mentoring of Santi Batik MSMEs through Digital Marketing Strategies Based on Sharia Principles - Astri Rahma Yustianah; Sri Wahyuni; Ade Agus Setiawan; Uswatun Hasanah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to comprehensively analyze the empowerment and mentoring process received by the Santi Batik MSME and examine the implementation of a digital marketing strategy based on Sharia principles within the framework of community-based business development. Using a descriptive qualitative approach with a case study method, data were obtained through in-depth interviews, participant observation, and documentation review conducted throughout 2024. The findings indicate that the community-based empowerment program significantly improved managerial capacity and production skills, particularly in financial management, product innovation, and market adaptation. The mentoring process, which was continuous and contextual, proved effective in fostering business independence and strengthening the economic resilience of MSME actors in facing market challenges. In the digital aspect, Santi Batik has successfully utilized social media and online marketplaces as marketing channels while integrating Islamic ethical values such as honesty, transparency, fairness, and social responsibility. These principles are reflected in promotional content, pricing strategies, and interactions with customers. The integration of Sharia values into digital marketing not only enhances consumer trust but also builds a distinctive and sustainable brand identity. Overall, this study contributes both conceptually and practically to the development of a Sharia-based MSME empowerment model in the digital era, while also offering guidance for policymakers and mentoring practitioners in designing inclusive and value-driven business development programs.